Patient after renal transplantation with syncope: Role of echocardiography in upright position. Issue 9 (8th March 2017) - Dimitrow, Paweł Petkow; Sorysz, Danuta; Hładij, Rafał; Chyrchel, Bernadeta; Dudzik, Barbara; Sułowicz, Władysław; Surdacki, Andrzej
ABSTRACT: In Doppler echocardiography, testing left ventricular outflow tract (LVOT) gradient in the supine position (as is done in everyday practice) does not reflect the pathophysiology of this dynamic abnormality during the daily activities that trigger the symptoms (eg, syncope). LVOT obstruction is a dynamic phenomenon, strongly dependent on the left ventricular cavity size, geometric configuration of hypertrophy, load variability, contractility, and mitral apparatus abnormalities. LVOT gradient may develop not only in hypertrophic cardiomyopathy but also in various heart diseases. Recent investigations show that LVOT gradient should be measured also in the standing position. Here, we report the case of patient after renal transplantation, who developed LVOT gradient during orthostatic test. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45 :616–620, 2017